Relationship Professional Competence of Geography Teachers with Spatial Thinking Students in Pandeglang District High School - Nugraha, Dida Dwi; Maryani, Enok; Setiawan, Iwan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
This study aims to determine the relationship of the professional competence of geography teachers with the ability of spatial thinking students in Pandeglang District High School. This study uses a survey method where this method is a method that aims to collect large amounts of data in the form of variables, units or individuals at the same time. Research using this method is intended to obtain a detailed picture of the Relationship of Professional Competence of Geography Teachers with Spatial Thinking of students in Pandeglang District High School. The subjects in this study were students of class XII IPS in several schools in Pandeglang District High School. The instrument used was a Likert scale to determine the professional competence of geography teachers according to students ‘perceptions and multiple-choice questions for abilities spatial thinking students’. Based on the results of data analysis, it was concluded that: (1) the average percentage of professional competencies of geography teachers according to students’ perceptions was 88.23% with very high criteria; (2) the average percentage of abilities spatial thinking students’ is 81.87% with very high criteria; (3) there is a positive relationship between the professional competence of geography teachers and the ability of spatial thinking students with a significance value of 0,000 and the value Pearson correlation of 0.973 at a very strong degree of relationship.